PM2.5, Fine Particulate Matter: A Novel Player in the Epithelial-Mesenchymal Transition? - Xu, Zihan; Ding, Wenjun; Deng, Xiaobei (Frontiers in Physiology, 2019)
Epithelial-mesenchymal transition (EMT) refers to the conversion of epithelial cells to mesenchymal phenotype, which endows the epithelial cells with enhanced migration, invasion, and extracellular matrix production abilities. These characteristics link EMT with the pathogenesis of organ fibrosis and cancer progression. Recent studies have preliminarily established that fine particulate matter with an aerodynamic diameter of less than 2.5 μm (PM2.5) is correlated with EMT initiation. In this pathological process, PM2.5 particles, excessive reactive oxygen species (ROS) derived from PM2.5, and certain components in PM2.5, such as ions and polyaromatic hydrocarbons (PAHs), have been implicated as potential EMT mediators that are linked to the activation of transforming growth factor β (TGF-β)/SMADs, NF-κB, growth factor (GF)/extracellular signal-regulated protein kinase (ERK), GF/phosphatidylinositol 3-kinase (PI3K)/Akt, wingless/integrated (Wnt)/β-catenin, Notch, Hedgehog, high mobility group box B1 (HMGB1)-receptor for advanced glycation end-products (RAGE), and aryl hydrocarbon receptor (AHR) signaling cascades and to cytoskeleton rearrangement. These pathways directly and indirectly transduce pro-EMT signals that regulate EMT-related gene expression in epithelial cells, finally inducing the characteristic alterations in morphology and functions of epithelia. In addition, novel associations between autophagy, ATP citrate lyase (ACLY), and exosomes with PM2.5-induced EMT have also been summarized. However, some debates and paradoxes remain to be consolidated. This review discusses the potential molecular mechanisms underlying PM2.5-induced EMT, which might account for the latent role of PM2.5 in cancer progression and fibrogenesis.